Pengaruh Representativeness Bias dan Availability Bias terhadap Pengambilan Keputusan Investasi - Maiziyah, Anindya Radita; Helmayunita, Nayang (Universitas Negeri Padang, 2023)
This research aims to determine and analyze the influence of representativeness and availability on investment decisions. This research is included in the type of associative causality research using a quantitative approach. Researchers collected data using a questionnaire distributed to 349 respondents from UNP, UNAND and PNP accounting students. The data used in this research is primary data. Hypothesis testing in this research uses multiple linear regression analysis with IBM SPSS. Based on research findings and discussions, the following conclusions can be drawn: Representativeness influences investment decisions significantly and positively. This shows that the first hypothesis (H1) proposed can be accepted. Availability influences investment decisions positively and significantly. This means that the first hypothesis (H1) proposed is accepted.